SMALL AND MEDIUM-SIZED ENTERPRISES IN REPUBLIC OF MOLDOVA - Igor G. SÎRODOEV (Journal of Urban and Regional Analysis, 2009)
The paper examines the role of SME sector in Moldova’s economy and its likely implications in the RD processes. There are emphasized several key features of the relationship between knowledge economy, RD and SMEs, and their effect on regional and local communities. Then, a summary of RD particular features in Moldova is presented.The role of SME sector, examined in terms of its performance by ownership and activity types, as a whole and by main firms’ categories (micro-, small, and medium-sized) is analyzed. Small enterprises have been considered as the most adequate solution forpromoting RD in general case. National-level analysis is completed by regional insight into the sector as a whole. Finally, some critical aspects of SMEs’ role in RD in Moldova are discussed.